2009
DOI: 10.1007/978-3-642-02812-0_31
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Cognitive Task Load and Performance of Naval Operators

Abstract: Operators on naval ships have to act in dynamic, critical and highdemand task environments. For these environments, a cognitive task load (CTL) model has been proposed as foundation of three operator support functions: adaptive task allocation, cognitive aids and resource feedback. This paper presents the construction of such a model as a Bayesian network with probability relationships between CTL and performance. The network is trained and tested with two datasets: operator performance with an adaptive user i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 5 publications
(5 reference statements)
0
6
0
Order By: Relevance
“…Other studies have done similar research, but within different context and with different methods. As a first example, Neerincx et al (2009) created a naïve Bayesian network to predict performance of naval operators. The COPE model includes Neerincx' model, addressing more factors and distinguishing several error types, and can therefore be used for training purposes.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have done similar research, but within different context and with different methods. As a first example, Neerincx et al (2009) created a naïve Bayesian network to predict performance of naval operators. The COPE model includes Neerincx' model, addressing more factors and distinguishing several error types, and can therefore be used for training purposes.…”
Section: Discussionmentioning
confidence: 99%
“…Neerincx et al [20] showed that the cognitive states recognized by this model (optimal, underload, overload, cognitive lock-up and vigilance) affected performance, and that the model could be successfully used to estimate performance, with an accuracy of 86% in a laboratory setup, and 74% aboard a naval ship. (Neerincx, 2003) Using only three metrics makes it easier for an expert to rate the tasks, and allows for automatic estimation of the cognitive state.…”
Section: The Ctl-model: Overviewmentioning
confidence: 98%
“…An important challenge in adaptive automation is deciding when to change the level of autonomy of the robot, and to which level. This can be done based on the cognitive task load of the operator (Neerincx, 2003), as cognitive task load has an influence on performance (Neerincx et al, 2009). In addition, cognitive task load itself is influenced by changing levels of automation, as the level of autonomy and operator task load are inversely correlated if other factors remain stable (Steinfeld et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Being in such a state has a negative influence on performance. The CTL model has been experimentally validated in the naval domain (Neerincx et al, 2009).…”
Section: Introductionmentioning
confidence: 99%